Improving Literacy Outcomes for Disadvantaged Girls Through Empowerment: The Case of Siyani Sahelian Programme in Pakistan - Aslam, Monazza; Cashman, Laura; Hamid, Moaaz; Rawal, Shenila; Jamil, Baela Raza; Sabates, Ricardo; Saeed, Saba (Poverty Impacts on Literacy Education, 2022)
Literacy acquisition is important for the formation of higher order skills, further engagement with written forms of knowledge, and deeper participation in society. Yet not all children have the opportunity to acquire literacy skills in their own mother tongue to allow them to continue to advance to...